Pengaruh Faktor Keuangan dan Non Keuangan Terhadap Semangat Kerja Karyawan PT. Enseval Putera Megatrading Tbk. Cabang Banda Aceh - Faisal Faisal; Darnelly Darnelly; Isthafan Najmi (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This study is an empirical study that aims to determine the effect of Financial Factors on Employee Morale at PT. Enseval Putera Megatrading Tbk. Banda Aceh Branch and to determine the effect of Non-Financial Factors on Employee Morale at PT. Enseval Putera Megatrading Tbk. Banda Aceh Branch. The data analysis technique in this study uses multiple linear regression to analyze the effect of independent variables on dependent variables with the model Y = a + b1X1 + b2X2 + e. Research data were collected through a list of questions/questionnaires and documentation studies. Hypothesis testing using multiple linear regression analysis, F test (simultaneous) and t test (partial) is intended to determine simultaneously and partially the effect of independent variables on dependent variables. The object of this study is about Financial Factors, Non-Financial, Employee Morale at PT. Enseval Putera Megatrading Tbk. Banda Aceh Branch. The sample size of this study was 60 employees. The results of the study showed that the simultaneous test between the Financial and Non-Financial Factors had an effect on Employee Morale at PT. Enseval Putera Megatrading Tbk. Banda Aceh Branch. Then partially, namely the variables of Financial and Non-Financial Factors have a significant effect on Employee Work Spirit of PT. Enseval Putera Megatrading Tbk. Banda Aceh Branch